DAMPAK BI RATE, TINGKAT SUKU BUNGA, NILAI TUKAR, DAN INFLASI TERHADAP NILAI OBLIGASI PEMERINTAH - Ichsan Ichsan; Ghazali Syamni; Nurlela Nurlela; A. Rahman (University of Merdeka Malang, 2013)
The purpose of this study was to examine the influence of BI rate, SBI interest rate, inflation and the exchange rateto value of government bonds in Indonesia Stock Exchange. Data used in this study were secondary data in BIrate, SBI interest rates, inflation and the exchange rate period January 2007 to October 2012. The methods of dataanalysis were multiple regression models and they were analyzed using IBM SPSS software version 20. Theresults showed that partially only the exchange rate that did not significantly influence the value of governmentbonds. This finding could be explained that the exchange rate had no effect related to central bank intervention(Bank Indonesia) to move the exchange rate at the time of depreciation or appreciation.